2021
DOI: 10.1007/s11881-021-00214-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring sources of poor reading comprehension in English language learners

Abstract: This study examined the sources of reading comprehension difficulties in English language learners (ELLs). The characteristics of ELL poor comprehenders were compared to their English as a first language (EL1) peers. Participants included 124 ELLs who spoke Chinese as an L1 and 79 EL1 students. Using a regression technique based on age, non-verbal reasoning, word reading accuracy, and word reading fluency, three types of comprehenders (poor, average, and good) were identified within each language group. The gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 73 publications
(120 reference statements)
3
30
0
Order By: Relevance
“…As previously stated, morphological awareness is a skill that continues to develop throughout the school years ( Casalis and Louis-Alexandre, 2000 ), along with reading expertise ( Rastle, 2019 ). In addition, several studies demonstrated its relationship with reading comprehension, since it contributes significantly to knowing the meaning of words, thus favoring the understanding of the text (e.g., Deacon and Kirby, 2004 ; Cain and Oakhill, 2006 ; D’Alessio et al, 2019 ; Zhang et al, 2020 ; Li et al, 2021 ). However, the study of Zhang et al (2020) supports that the contribution of morphological awareness depends on language proficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously stated, morphological awareness is a skill that continues to develop throughout the school years ( Casalis and Louis-Alexandre, 2000 ), along with reading expertise ( Rastle, 2019 ). In addition, several studies demonstrated its relationship with reading comprehension, since it contributes significantly to knowing the meaning of words, thus favoring the understanding of the text (e.g., Deacon and Kirby, 2004 ; Cain and Oakhill, 2006 ; D’Alessio et al, 2019 ; Zhang et al, 2020 ; Li et al, 2021 ). However, the study of Zhang et al (2020) supports that the contribution of morphological awareness depends on language proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological awareness is defined as the ability to manipulate morphemes and the structure of words ( Kuo and Anderson, 2006 ). This metalinguistic consciousness, especially considering derivational morphology, continues to develop throughout schooling ( Casalis and Louis-Alexandre, 2000 ), and it is important to achieve word meanings, in turn then favoring reading comprehension ( McBride-Chang et al, 2003 ; Deacon and Kirby, 2004 ; Cain and Oakhill, 2006 ; Guo et al, 2011 ; Jeon and Yamashita, 2014 ; Tong et al, 2014 ; D’Alessio et al, 2019 ; Zhang et al, 2020 ; Kotzer et al, 2021 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is logical to operationalize syntactic awareness as word order knowledge using a word order knowledge test. In addition to word order knowledge, previous research in L1 Chinese and L2 English reading has also shown that the ability to detect and correct grammatical errors accounted for a significant amount of unique variance in L1 Chinese (e.g., Chik et al, 2012) and L2 English reading comprehension (e.g., Li et al, 2021). Grammatical judgment and correction test could tap into different aspects of Chinese syntactic knowledge such as function words, conjunctions, tense markers, classifiers, particles, prepositions, and copula words.…”
Section: 一起mentioning
confidence: 99%
“…They find that for college students with discrepant levels of reading comprehension and decoding, vocabulary and morphological awareness appear to be protective factors, thus enabling adequate comprehension of text despite relatively weak decoding skills. Previous studies have shown that morphological awareness is generally weak in poor comprehenders (e.g., Tong et al, 2014) and Li et al (2021) found that morphological awareness is lower in ELL poor comprehenders than in English as a first language (EL1) poor comprehenders; conversely, the findings of Farris et al indicate that morphological awareness may play a role in mitigating word-level deficits for those readers who have effectively bypassed developing strong decoding skills and still attained relatively strong reading comprehension. Farris and Odegard's findings indicate that further understanding what allows for unexpectedly proficient comprehension may provide both theoretically and practically informative insights about reading comprehension.…”
mentioning
confidence: 93%
“…The third set of papers explores the influence of readers' English language learner (ELL) status (Li et al, 2021;Martinez-Lincoln et al, 2021). ELL status in particular, versus other categories of students, is linked to reading comprehension because ELLs often show an S-RCD-like profile (Farnia & Geva, 2013;Lesaux et al, 2006), with stronger word-level processes than their reading comprehension proficiency would suggest.…”
mentioning
confidence: 99%